Elevated expression of miR-210 predicts poor survival of cancer patients: a systematic review and meta-analysis. - Jian Wang; Jiqing Zhao; Mengjing Shi; Yu Ding; Huiqin Sun; Fahuan Yuan; Zhongmin Zou (PLoS ONE, 2014)
Background MiRNAs are important regulators of different biological processes, including tumorigenesis. MiR-210 is a potential prognostic factor for survival in patients with cancer according to previous clinical researches. We conducted a systematic review and meta-analysis to summarize the significance of increased miR-210 expression in the prognosis of indicated cancers. Methodology/principal findings The present systematic review and meta-analysis of 16 researches included 1809 patients with 7 different types of cancers from 7 countries, and aimed to explore the association between miR-210 expression and the survival of cancer patients. Over-expression of miR-210 may predict poor overall survival (OS, HR = 1.33, 95% CI: 0.85-2.09, P = 0.210), but the effect was not significant. While the predictive effect on disease-free survival (DFS, HR = 1.89, 95% CI: 1.30-2.74, P = 0.001), progression-free survival (PFS, HR = 1.20, 95% CI: 1.05-1.38, P = 0.007) and relapse-free survival(RFS, HR = 4.42, 95% CI: 2.14-9.15, P = 0.000) for patients with breast cancer, primary head and neck squamous cell carcinoma (HNSCC), renal cancer, soft-tissue sarcoma, pediatric osteosarcoma, bladder cancer or glioblastoma was certain. Subgroup analysis showed the limited predictive effect of over-expressed miR-210 on breast cancer OS (HR = 1.63, 95% CI: 0.47-5.67, P = 0.443), breast cancer DFS (HR = 2.03, 95% CI: 0.90-4.57, P = 0.088), sarcoma OS (HR = 1.24, 95% CI: 0.20-7.89, P = 0.818) and renal cancer OS (HR = 1.16, 95% CI: 0.27-4.94, P = 0.842). Conclusions/significance This systematic review and meta-analysis suggests that miR-210 has a predictive effect on survival of patients with studied cancer types as indexed by disease-free survival, progression-free survival and relapse-free survival. While the predictive effect on overall survival, breast cancer overall survival, breast cancer disease-free survival, sarcoma overall survival and renal cancer overall survival was not statistically significant.